Surface and satellite observations of air pollution in India during COVID-19 lockdown: Implication to air quality. (March 2021) - Sathe, Yogesh; Gupta, Pawan; Bawase, Moqtik; Lamsal, Lok; Patadia, Falguni; Thipse, Sukrut
Graphical abstract: Highlights: COVID-19 Lockdown in India significantly improved air quality over many cities. Surface and satellite data shows 42–60 % reduction in PM2.5 and 46–61 % in NO2 . Improved AQI (21–56 %) benchmarks the opportunity for Air Quality policy changes. Abstract: The strict nationwide lockdown imposed in India starting from 25 th March 2020 to prevent the spread of COVID-19 disease reduced the mobility and interrupted several important anthropogenic emission sources thereby creating a temporary air quality improvement. This study conducts a multi-scale (national-regional-city), multi-species, and multi-platform analysis of air pollutants and meteorological data by synergizing surface and satellite observations. Our analysis suggests a significant reduction in surface measurements of nitrogen dioxide (NO2 ) (46–61 %) and fine particulate matter (PM2.5 ) (42–60 %) during the lockdown period that are also corroborated by the reduction in satellite observed aerosol optical depth (AOD) (3–56 %) and tropospheric NO2 column density (25–50 %) data over multiple cities. Other species, namely coarse particulate matter (PM10 ) (24–62 %), ozone (22–56 %) also showed a substantial reduction whereas carbon monoxide (16–46 %), exhibited a moderate decline. In contrast, sulfur dioxide (SO2 ) levels did not show any defined reduction trend but rather increased in Mumbai, Bengaluru, and Kolkata. The temporary air quality improvement achieved by the painful natural experiment of this pandemic has helped demonstrate the importance of reducing emissions from other sectors along with transportation and industry to achieve the national air quality targets in the future.